2013
DOI: 10.1037/a0030907
|View full text |Cite
|
Sign up to set email alerts
|

Divided attention can enhance memory encoding: The attentional boost effect in implicit memory.

Abstract: Distraction during encoding has long been known to disrupt later memory performance. Contrary to this long-standing result, we show that detecting an infrequent target in a dual-task paradigm actually improves memory encoding for a concurrently presented word, above and beyond the performance reached in the full-attention condition. This absolute facilitation was obtained in 2 perceptual implicit tasks (lexical decision and word fragment completion) but not in a conceptual implicit task (semantic classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
114
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(129 citation statements)
references
References 46 publications
13
114
0
2
Order By: Relevance
“…The experiment replicated the results of Spataro et al (2013) in finding an ABE with verbal materials. More importantly, this experiment demonstrated that the ABE occurs with auditory recognition, and to the same degree as with a visual test, a first demonstration that the ABE generalizes over test modahty.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The experiment replicated the results of Spataro et al (2013) in finding an ABE with verbal materials. More importantly, this experiment demonstrated that the ABE occurs with auditory recognition, and to the same degree as with a visual test, a first demonstration that the ABE generalizes over test modahty.…”
Section: Discussionsupporting
confidence: 80%
“…First, the results of the visual testing condition replicate the results of Spataro et al (2013); The ABE was found in the DA condition but not in the FA condition. This replication is important because Spataro et al were the first report of an ABE using verbal rather than pictorial materials.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations